What and how? last-minute choice deflection in E-commerce - Errie Margery; Lusiah Lusiah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
The rise of e-commerce has fundamentally transformed consumer behavior, introducing dynamic, information-rich environments that influence purchasing decisions. This study explores the phenomenon of last-minute choice deflection, where consumers change their initial product preferences after being exposed to algorithmically curated alternatives on digital platforms. Using a quantitative approach through an experimental survey involving Generation Z respondents, this research investigates the roles of brand image, influencer marketing, price, loyalty, and customer reviews in shaping consumer decisions, focusing on body care products as the category of interest. Employing robust least squares regression, the findings reveal that customer reviews and competitive pricing significantly reduce choice deflection by reinforcing consumers’ initial preferences. Brand image shows a mildly significant effect, whereas influencer marketing and loyalty do not exhibit statistically significant impacts. These results offer insights for marketers aiming to design more persuasive strategies in online markets and contribute to consumer behavior theory by contextualizing decision-making dynamics in digital commerce.